2019
DOI: 10.18502/jovr.v14i3.4790
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Incidence and Ecological Determinants of Diabetic Retinopathy in Iran: Systematic Review and Meta-analysis

Abstract: Purpose To estimate the pooled prevalence and incidence of diabetic retinopathy (DR) in Iran and to investigate their correlations with the Human Development Index (HDI), healthcare access (i.e., density of specialists and sub-specialists), and methodological issues.Methods Electronic databases such as PubMed, Embase, Scopus, Web of Science, Google Scholar, and local databases were searched for cohort and cross-sectional studies published prior to January 2018. Prevalence and incidence rates of DR were extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Previous studies demonstrated that circ-PSEN1 is upregulated in DR [ 30–32 ]. On the basis of this finding, we intended to further investigate whether circ-PSEN1 functioned in the DR-induced ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that circ-PSEN1 is upregulated in DR [ 30–32 ]. On the basis of this finding, we intended to further investigate whether circ-PSEN1 functioned in the DR-induced ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a systematic review by Maroufizadeh et al [7], the prevalence of diabetic retinopathy in Iran (including general population, diabetic and eye clinics) was reported as 41.9% (95% CI 35.6-48.2). In another systematic review, the pooled prevalence of DR in population-based studies in Iran was 29.6% (95% CI 22.6-36.5) [8]. They showed that the rate was 31.8% (95% CI 24.5-39.2) in diabetic clinics and 57.8% (95% CI 50.2-65.3) in eye clinics.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, 17.52% had new onset diagnosis of diabetes. Other causes of these differences in DR prevalence are difference in methodology (including the screening tool; the prevalence may be [16,40,41], setting and risk of selection bias (the prevalence is the lowest in general population, primary healthcare facilities, diabetic or eye clinics, and hospitals) [7,8], diagnostic method (diagnosis of diabetes based on patient self-report, without laboratory testing, may overestimate the prevalence of DR due to the exclusion of undiagnosed diabetes from the sample) [8], sample size, ethnicity (ethnic variations may be due to related social and economic differences and access to diabetes care) [42], nutrition, demographic, and lifestyle [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intravitreal ranibizumab and bevacizumab are administrated for the treatment of CSME [ 10 ]. Diabetic retinopathy occurs in 1 out of 3 people with diabetes, with reported rates of DME reaching 7% in this group of patients [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%